Defining "volcanic necks" sites by field study In the southern part of Syrian coastal chain - إبراهيم سعيد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research include a study and definition to named ’volcanic necks’ situated in southern part of Syrian coastal chain (creating maps to Tartous, Safita, Alhamydiah, Halba, western part of Talkalah sheets and Alhosen Castle, scale ). Researcher achieved a field study to the volcanic rocks sitesrefer to the period of Pliocene in 78 supposed sites. To definition of volcanic necks in the study area. Through this study he found a certain 17 volcanic necks, in addition to uncertain 9 necks distributed in different places of the study area, which need a additional stories These led to important conclusion to assure that Pliocene volcanic activity, which happened in the southern Syrian rift zone, didn’t happen only in the eastern side of the rift, but also it included a different places of the western side. On the other side, we assured that, the different parts of lava which diffusepresently in the study area was formed by local volcanic activity, a not from the central volcanism situated on the eastern side of the rift named (Sheen plateau).